2007
DOI: 10.1002/cbf.1432
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oleic and linoleic acids on the inflammatory phase of wound healing in rats

Abstract: Inflammation is a crucial step for the wound healing process. The effect of linoleic and oleic acids on the inflammatory response of the skin during the healing process and on the release of pro-inflammatory cytokines by rat neutrophils in vitro was investigated. A wound in the dorsal surface of adult rats was performed and fatty acids were then topically administered. Both oleic and linoleic acids increased the wound healing tissue mass. The total protein and DNA contents of the wounds were increased by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
108
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 39 publications
(41 reference statements)
4
108
1
3
Order By: Relevance
“…Previous studies by Cardoso et al (2004) and Pereira et al (2008) indicated acceleration in the wound healing process in rats treated with n-6 fatty acids, as well as a tendency toward faster wound closure in rats receiving n-9 fatty acids. A tendency for delayed wound closure in rats treated with n-3 fatty acids was also observed.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…Previous studies by Cardoso et al (2004) and Pereira et al (2008) indicated acceleration in the wound healing process in rats treated with n-6 fatty acids, as well as a tendency toward faster wound closure in rats receiving n-9 fatty acids. A tendency for delayed wound closure in rats treated with n-3 fatty acids was also observed.…”
Section: Introductionmentioning
confidence: 83%
“…The animals were housed in cages (maximum of five per cage) maintained at 23 °C under a lighting regimen of 12/12 h. Food and water were given ad libitum (Pereira et al, 2008). All experiments were conducted according to the guidelines of the Animal Care Committees of the Institute of Biomedical Sciences and the Faculty of Pharmaceutical Sciences of the University of São Paulo (Protocol Numbers CEEA ICB/ USP 68-71-2 and CEEA FCF/USP 236).…”
Section: Animalsmentioning
confidence: 99%
See 3 more Smart Citations